Psychoactive substances have major impact on injuries in rural arctic Norway – A prospective observational study - Wilson, Thomas; Wisborg, Torben; Vindenes, Vigdis; Jamt, Ragnhild G.; Furuhaugen, Håvard; Bogstrand, Stig Tore (Acta Anaesthesiologica Scandinavica, 2021)
Background - Rural areas have increased injury mortality with a high pre-hospital death rate. Knowledge concerning the impact of psychoactive substances on injury occurrence is lacking for rural arctic Norway. These substances are also known to increase pre-, per- and postoperative risk. The aim was by prospective observational design to investigate the prevalence and characteristics of psychoactive substance use among injured patients in Finnmark county. Methods - From January 2015 to August 2016, patients ≥18 years admitted to hospitals in Finnmark due to injury were approached when competent. Blood was analysed for ethanol, sedatives, opioids, hypnotics and illicit substances in consenting patients, who completed a questionnaire gathering demographic factors, self-reported use/behaviour and incident circumstances. Results - In 684 injured patients who consented to participation (81% consented), psychoactive substances were detected in 35.7%, alcohol being the most prevalent (23%). Patients in whom substances were detected were more often involved in violent incidents (odds ratio 8.92 95% confidence interval 3.24-24.61), indicated harmful use of alcohol (odds ratio 3.56, 95% confidence interval 2.34-5.43), reported the incident being a fall (odds ratio 2.21, 95% confidence interval 1.47-3.33) and presented with a reduced level of consciousness (odds ratio 3.91, 95% confidence interval 1.58-9.67). Subgroup analysis revealed significant associations between testing positive for a psychoactive substance and being diagnosed with a head injury or traumatic brain injury. Conclusion - A significant proportion of injured patients had used psychoactive substances prior to admission. Use was associated with violence, falls, at-risk alcohol consumption, decreased level of consciousness on admittance and head injury.